Analysis Determining Factors of Profitability The Infrastructure, Utilities and Transportation Sector Firms - Amri Amrulloh; Halleina Rejeki Putri Hartono; Yopie Diondy Kurniawan; Amalia Kulsum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The infrastructure, utilities and transportation sectors play an important role in a country's economy. Profitability is a key indicator in assessing the performance of companies in this sector. However, achieving profitability is faced with various challenges, including large capital investments, high operating costs, strict government regulations, and changes in global economic conditions. This study uses a literature study method to analyze the factors that affect the profitability of companies in the infrastructure, utilities, and transportation sectors. The results of the analysis show that financial factors, operational efficiency, technology, regulations, and external conditions such as market demand and global energy prices play a significant role in determining the level of profitability. Companies that are able to manage their capital structure, utilize technology, and adapt to regulations and dynamic economic conditions have a great opportunity to improve their financial performance. This study provides in-depth insights into how companies can manage internal and external factors to achieve sustainable profitability.